LAYANAN BIMBINGAN KELOMPOK BERBASIS PERMAINAN (TEBAK KATA) DALAM MENINGKATKAN KOMUNIKASI INTERPERSONAL SISWA - saragih, Rama Suryani Br; Saam, Zulfan; Donal, Donal (Universitas Borneo Tarakan, 2022)
Interpersonal communication is a communication process carried out between two or more people, can be done directly and can be done indirectly or using the media. Group guidance services and guessing games can be used as an alternative in learning so that students' speaking skills can also improve. The purpose of this study was to see whether there was a significant effect and difference before and after being given group guidance services in improving students' interpersonal communication with games (guessing words). This research is a quantitative research with the experimental method with the type of experiment Pre-Experimental Designs (Nondesigns) using the One-Group Pretest-Posttest Design. The research subjects used purposive sampling technique by considering certain things and did a pretest using a Likert scale instrument and obtained 7 students of class VIII 6 SMP Negeri 016 Pekanbaru who got the results of posttest vulnerable scores 46. Data analysis to test differences using the Wilcoxon test and to test the effect by using the Spearman rank test. The results showed that there was a significant influence and there were differences in students' interpersonal communication before and after being given group guidance services based on guessing games.Keywords : group guidance, interpersonal communication, gemes